Fundamentals of air cleaning technology and its application in cleanrooms - Xu, Zhonglin (Springer Berlin Heidelberg, 2014)
Fundamentals of Air Cleaning Technology and Its Application in Cleanrooms sets up the theoretical framework for cleanrooms. New ideas and methods are presented, which include the characteristic index of cleanrooms, uniform and non-uniform distribution characteristics, the minimum sampling volume, a new concept of outdoor air conditioning and the fundamentals of leakage-preventing layers. Written by an author who can look back on major scientific achievements and 50 years of experience in this field, this book offers a concise and accessible introduction to the fundamentals of air cleaning technology and its application. The work is intended for researchers, college teachers, graduates, designers, technicians and corporate R&D personnel in the field of HVAC and air cleaning technology. Zhonglin Xu is a senior research fellow at China Academy of Building Research.